Instruments For Assessment Of Excessive Daytime Sleepiness In Brazilian Children And Adolescents: Systematic Review - Bajerski,Andrei Eduardo (2022)
Abstract Objective: To systematically review the literature on the instruments used to assess excessive daytime sleepiness (EDS) in Brazilian children and adolescents. Data source: A systematic review of the literature was performed in the databases MEDLINE PubMed, Scopus, Web of Science, LILACS, Scielo and SPORTDiscus, with no time limit for searches. The eligibility criteria were studies published in English and Portuguese, original articles that used questionnaires to assess EDS and whose sample consisted of Brazilian children and/or adolescents. As search strategy, the following terms were combined with Boolean operators “OR” and/or “AND”: drowsiness, disorders of excessive somnolence, excessive daytime sleepiness, day sleepiness, midday sleepiness, daytime sleepiness, adolescents, Brazil, Brazilian adolescents, and children. Data synthesis: Sixteen articles were selected, in which nine different instruments were applied to 8.240 children and adolescents from the South, Southeast, Midwest and Northeast regions of Brazil. The mean of methodological quality of studies was 16.1±1.9 points. The instruments most frequently used were the Pediatric Daytime Sleepiness Scale (PDSS) and Karolinska Sleepiness Scale (KSS), but only PDSS was shown reliable to assess EDS in Brazilian children and adolescents. Conclusions: The PDSS was the only instrument considered reliable to assess EDS in Brazilian children and adolescents. Further research on EDS in children and adolescents are suggested to perform the validation of other instruments for Brazil and present internal consistency values.